(untitled) - Sakaiya, Taichi (New York, NY., 1993)
In a witty, acerbic, and provocative book, the author of the influential futurist synthesis The Knowledge-Value Revolution shows how Japan, borrowing elements from both China and the West, has created a culture unlike any other--one that is still changing in a uniquely Japanese way.
Keywords: Japan; Civilization